A Survey on Skills of DevRel professionals - Cunha, Ana Elisa da Silva; Cafeo, Bruno B. P.; Viana, Davi; Fontão, Awdren (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2022: Anais do XVIII Simpósio Brasileiro de Sistemas de Informação, 2022)
Context: Developer Relations (DevRel) is an organizational area responsible for maintaining synergy among developer communities and organizations. This team can be seen in companies like Amazon, Apple, Google, and Microsoft, with a business model based on software ecosystems (SECO). A DevRel team has roles that perform specific activities (e.g., hackathons, developer programs) to achieve the organization's goals and a better developer experience. Problem: The lack of clarity regarding the nature and set of skills needed by a DevRel professional can negatively impact the performance of related activities and consequently the purpose of SECO. Solution: We investigated a set of DevRel skills for education/training purposes. IS theory: This paper was generated from the perspective of the Theory of Organizational Creativity. This theory provides the key to understanding organizational effectiveness and survival. Method: We performed an opinion survey with 24 participants from ten countries. Results: The nature of DevRel's professional skills is soft skills in which communication, willingness to learn, teamwork, interpersonal, and listening skills stand out. Hard skills have their share of contribution to DevRel activities and marketing and software programming/development skills stand out. Contributions and Impact in the IS area: The main contribution of the paper is to make a product viable for any organization or individual to be able to develop the skills of a DevRel professional. Topics: Digital and business ecosystems